Numerical investigations on CdTe-based rectangular photonic waveguides - Istiak Ahmed Rasel; Md. Alamin Hossain Pappu; Jaker Hossain (Physics Open)
Cadmium telluride (CdTe)-based photonic waveguides featuring an H-bend have been designed and computed in detail by COMSOL Multiphysics at an operating wavelength of 1.55 μm. The structure includes CdTe as the core material, SiO2 as the cladding, and ZnO as the substrate. The overall dimension of the waveguide is (4 × 3) μm where the core width and height are 1.2 μm and 0.8 μm while the substrate height is 1 μm. Several performance parameters have been evaluated, including the power confinement factor (PCF), optical loss, effective mode index (neff), and electric field distribution, across varying wavelengths and dimensions of the core and cladding. The waveguides exhibit impressive PCF values of 98.65 % for the TE and 96.54 % for the TM modes. The value of PCF decreases to 86 % at a wavelength of 2.5 μm for both TE and TM modes. The loss values are calculated as −0.895 dB/cm and −0.94 dB/cm, for the TE and TM modes, respectively. The neff are determined to be 2.53 and 2.55 for the TE and TM modes, respectively. The remarkable properties of CdTe-based photonic waveguides including a high PCF and low optical losses hold great potential for applications in optical communication, mid-infrared photonics, and quantum photonics.